Mainstreaming Agama, Kesehatan dan Masyarakat melalui Tabligh Akbar “ Sehat Mudah Murah Sesuai Syariah“ di Jami Al-Huda Tebet Timur - Fajar Aditiya Nugraha; Muhamad Ridho Pratama; Akhmad Kanzulfikar; Razan Qaedi; Hayiz Historia Adhi Pratama; Lisy Tantowi (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
On these days, religious is predicted to be overcasted due to the presence of modernity in life. However, the point of view has been sluggishly dissipated with a new concept that organizes the religious and modernity in harmony. Health aspect is one of the main entity. Muhammadiyah truly pays attention to the health aspect. Until year 2023, Muhammadiyah has 373 hospitals and clinics. Thus, the event ‘Tabligh Akbar‘ titled “Sehat Mudah Murah Sesuai Syariat“ held on May 6th 2025 is the real action from Muhammadiyah to society. ‘Tabligh Akbar‘ is conducted by Branch Board of Muhammadiyah Tebet Timur and Branch Board of Aisyiyah Tebet Timur with the main speaker dr. Zaidul Akbar. The event is considered successful because there were 500 people attended from public society and  regular congregation. The key factors that makes the event successful are the Muhammadiyah itself, the main speaker, and the promotion media that was well-widely distributed. From the aspect of dissemination information, the attendants got the information from social media. Besides, there were many anttendants gor the information from the banner that is planted on surrounded event location. The other success parameter of the event is known by the enthusiasm from the attendants who were really active on question answer session with dr. Zaidul Akbar and the attendants confession who tried the recipes from dr. Zaidul Akbar on the spot.